NO2 Sensing with SWCNT Decorated by Nanoparticles in Temperature Pulsed Mode: Modeling and Characterization - Enza Panzardi; Anna Lo Grasso; Valerio Vignoli; Marco Mugnaini; Pietro Lupetti; Ada Fort (Sensors, 2020)
In this paper, NO2 sensing by means of single-wall carbon nanotubes (SWCNT) networks, decorated with nanoparticles of TiO2 and Au, is proposed. In particular, it is shown that the performance of these materials can be enhanced using pulsed temperature mode. This sensing strategy effectiveness is theoretically and experimentally assessed. In this paper, in fact, a dynamic model for conductive gas sensors formed by networks of nanowires, considering the junctions between different wires as the main contribution to sensor conductance, and in the presence of the target gas, is presented and validated. The model accounts for variable temperature and gas concentration and sheds some light on the mechanisms leading to the sensor response improvement related to temperature pulsed working mode. It is also shown how the addition of a different material can be modeled through different surface adsorption kinetics.